Five cases of sarcoidosis in one family: a new immunological link?. Issue 4 (1st April 2000) - Elford, J; Fitch, P; Kaminski, E; McGavin, C; Wells, I P
Abstract : We report a family in which five members have been affected with sarcoidosis. The radiological findings of all cases are presented, together with HLA typing, T cell subset and cytokine analysis in four cases. A new HLA association in the presentation of sarcoidosis is suggested.